Associação de Eremanthus erythropappus (DC.) McLeish (Asteraceae) com formigas e sua relação com a mirmecofauna do solo em floresta de altitude, região central de Minas Gerais (Lundiana: International Journal of Biodiversity, 2009)
Ants occuring on Eremanthus erythropappus (“candeia”) and the ground were studied at an altitude forest. Forty-eight individuals of E. erythropappus were sampled, with manual sampling on the plants and baits on the adjacent soil. The ground fauna presented highest richness, diversity and equitability than plants. Two Camponotus species were dominant on plants. The association between ants and E. erythropappus is facultative, apparently with opportunistic use of exudates, and with the most common species co-occuring on plants and ground. The benefits of this association for the plants still need to be studied. E. erythropappus is a plant of economical interest, and the knowledge of the association with ants could be useful for its management.